Geomorphology of the Rio Cisles basin (Odle Group, Dolomites, Italy) - Paola Coratza; Alessandro Ghinoi; Mauro Marchetti; Mauro Soldati (Journal of Maps, 2019)
The results of geomorphological investigations carried out in the Rio Cisles basin in the Odle Group (Italian Alps) are presented. This is one of the most famous and spectacular mountain groups of the Dolomites, located in the north-western sector of the Gardena valley, an area of high tourism appeal. Field surveys and multitemporal aerial-photo interpretation led to the production of a geomorphological map at a 1:12,000 scale. This map outlines the features of an area of about 20 km2, characterised by high relief energy, mainly due to the overlapping of large dolomite rocks masses on clayey rocks. The present morphology is the result of intense postglacial and paraglacial geomorphic activity, which has affected the area since the Upper Pleistocene. The geomorphological evolution of this area has been reconstructed and a new contribution is given to the comprehension of the geomorphology of the eastern Dolomites.